The influence of void distribution on transverse mechanical properties of unidirectional composites - Bo Li; Meiying Zhao; Xiaopeng Wan (2017 8th International Conference on Mechanical and Aerospace Engineering (ICMAE), 2017)
The influence of void distribution on the transverse mechanical properties of unidirectional composites is studied. Firstly, using Matlab to obtain composites microscopic voids radius distribution. Secondly, based on void radius distribution, the representative volume element (RVE) of composites microstructure with random fiber, matrix, and random voids are generated by random algorithm. Finally, considering the elasticity-plasticity of matrix and bilinear traction-separation law for interface, the effect of void distribution on transverse behavior of unidirectional composites is simulated by the finite element analysis. It is found that the influence of the void distribution on transverse modulus, transverse tension strength and transverse compressive strength is small relatively, but the effect on the damage initiation, damage evolution and final damage of composite microstructure under transverse tension is large relatively.